Electrodeposited poly(phenylene oxide) suppresses anodic parasitic processes in carbon-based supercapacitor electrodes operating in an aqueous electrolyte - Baptista, Joana M.; Gaspar, Guilherme; Wijayantha, Upul K. G.; Lobato, Killian (Elsevier, 2022)
Aqueous electrolytes, when compared to organic electrolytes, are safer, cheaper and usually enable a higher capacitance and lower internal resistance. However, their narrow operational voltage window (ca. 1.2 V) limits the device's energy density and, as such, their current commercial use is limited. Poly(phenylene oxide) was electrodeposited on the surface of activated carbon electrodes and has been shown to decrease the anodic parasitic current. The impact on the cathodic parasitic current was minimal. Comparison of the polarisation curves obtained in 1 M Na2SO4 (aq) for coated and uncoated electrodes between 0.5 V and 1.1 V vs Ag|AgCl demonstrated a >66% decrease in the exchange current density of anodic processes (from 10.1 μA/cm2 to 3.4 μA/cm2). Assuming supercapacitor degradation is proportional to the parasitic faradaic current, this change in the anodic parameters enables a 31% increase in the upper positive potential when a maximum parasitic current density of 29 μA/cm2 is considered acceptable. When these coated electrodes were mounted as symmetrical coin cells and operated at an increased voltage window of 1.5 V (up from 1.2 V), gains in energy and power densities were from 2.2 Wh/kg to 4.6 Wh/kg and 159 W/kg to 465 W/kg, respectively.
Keywords: Supercapacitor; Aqueous electrolytes; Operational voltage; Passivation; Poly(phenylene oxide); Electropolymerization